Occurrence and concentration of agricultural phytosanitary residues in bivalve mollusks collected from Golfo Nuevo, Argentina - Frydman, Camila Ayelén; Gonzalez, Cintia Natalia; Pesquero, Natalia; Ruiz, María Juana; Barbieri, Elena Susana; Mozgovoj, Marina Valeria; Cristos, Diego Sebastian (Elsevier, 2026)
Agricultural phytosanitary products reach coastal bivalve mollusks via surface runoff and the deposition of wind-borne dust. We evaluated the occurrence and concentration ranges of 57 commonly used phytosanitary compounds in bivalve mollusks from three sampling sites in Golfo Nuevo, Chubut Province, Argentina. All soft tissues were homogenized and extracted using a modified QuEChERS protocol. Extracts were subsequently analyzed by liquid chromatography–mass spectrometry (LC–MS) and gas chromatography–mass spectrometry (GC–MS). Based on the analyses, all samples contained at least one pesticide residue. Of the 57 compounds investigated, 28 exceeded the European Union's default maximum residue limit of 10 μg kg−1, this value is used here as a comparative benchmark in the absence of specific limits for bivalves, and it does not necessarily represent a toxicological threshold for marine organisms. Herbicides were the most prevalent class and consistently presented the highest concentrations across the three-year study period, followed by fungicides and, to a lesser extent, insecticides. These findings provide the first systematic baseline of phytosanitary contamination-mediated by both atmospheric deposition and runoff-in bivalve mollusks from Golfo Nuevo and highlight the need for integrated monitoring and risk management strategies.